Establishment of Sf9 Transformants Constitutively Expressing PBAN Receptor Variants: Application to Functional Evaluation - Lee, Jae M.; Hull, J. J.; Kawai, Takeshi; Tsuneizumi, Kazuhide; Kuriharaa, Masaaki; Tanokura, Masaru; Nagata, Koji; Nagasawa, Hiromichi; Matsumoto, Shogo (Frontiers in Endocrinology, 2012)
To facilitate further evaluation of pheromone biosynthesis activating neuropeptide receptor (PBANR) functionality and regulation, we generated cultured insect cell lines constitutively expressing green fluorescent protein chimeras of the recently identified Bombyx mori PBANR (BommoPBANR) and Pseudaletia separata PBANR (PsesePBANR) variants. Fluorescent chimeras included the BommoPBANR-A, B, and C variants and the PsesePBANR-B and C variants. Cell lines expressing non-chimeric BommoPBANR-B and C variants were also generated. Functional evaluation of these transformed cell lines using confocal laser microscopy revealed that a Rhodamine Red-labeled PBAN derivative (RR-C10PBANR2K) specifically co-localized with all of the respective PBANR variants at the plasma membrane. Near complete internalization of the fluorescent RR-C10PBANR2K ligand 30 min after binding was observed in all cell lines except those expressing the BommoPBANR-A variant, in which the ligand/receptor complex remained at the plasma membrane. Fluorescent Ca2+ imaging further showed that, unlike the BommoPBANR-B or BommoPBANR-C cell lines, RR-C10PBANR2K binding failed to mobilize extracellular Ca2+ in the BommoPBANR-A cell line even at concentrations of 10 M. These observations demonstrate a clear functional difference between the BommoPBANR-A variant and the BommoPBANR-B and –C variants in terms of receptor regulation and activation of downstream effector molecules. We also found that, contrary to previous reports, ligand-induced internalization of BommoPBANR-B and BommoPBANR-C in cell lines stably expressing these variants occurred in the absence of extracellular Ca2+.